Fabrication of chiral mesoporous carbonaceous nanofibers and their electrochemical energy storage. (20th September 2016) - Sun, Huayan; Wang, Qing; Geng, Hongbo; Li, Baozong; Li, Yi; Wu, Qi-Hui; Fan, Jingmin; Yang, Yonggang
Abstract: Chiral carbon-based nanomaterials possess many superior properties originated both from their nano-sized structure and their chirality. We presented a facile way to synthesize chiral mesoporous carbonaceous nanofibers (chiral MCNFs) through a supramolecular templating method, using a pair of chiral low-molecular-weight gelators as the templates, resorcinol, formaldehyde and tetraethyl orthosilicate as the precursors, respectively. Besides, the chiral MCNFs exhibited optical activity; the electrochemical measurements implied that they also showed good capacitance and lithium-ion storage performances.